2014
DOI: 10.4049/jimmunol.1302567
|View full text |Cite
|
Sign up to set email alerts
|

Specific Recognition of Mycobacterial Protein and Peptide Antigens by γδ T Cell Subsets following Infection with VirulentMycobacterium bovis

Abstract: Promoting effective immunity to Mycobacterium bovis infection is a challenge that is of interest to the fields of human and animal medicine alike. We report that γδ T cells from virulent M. bovis–infected cattle respond specifically and directly to complex, protein, and nonprotein mycobacterial Ags. Importantly, to our knowledge, we demonstrate for the first time that bovine γδ T cells specifically recognize peptide Ags derived from the mycobacterial protein complex ESAT6:CFP10 and that this recognition requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 78 publications
2
43
0
Order By: Relevance
“…In prior studies, we demonstrated, with samples from a limited number of animals, that CD4 ϩ and ␥␦ ϩ T cells from M. bovisinfected cattle produced IL-17A in response to M. bovis PPD or rESAT-6:CFP10 (36). PPD-specific IL-17 mRNA responses at 60 and 90 days after experimental M. bovis infection correlated with the presence of gross tuberculous lesions at necropsy 4 months after challenge (7).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior studies, we demonstrated, with samples from a limited number of animals, that CD4 ϩ and ␥␦ ϩ T cells from M. bovisinfected cattle produced IL-17A in response to M. bovis PPD or rESAT-6:CFP10 (36). PPD-specific IL-17 mRNA responses at 60 and 90 days after experimental M. bovis infection correlated with the presence of gross tuberculous lesions at necropsy 4 months after challenge (7).…”
Section: Figmentioning
confidence: 99%
“…IFN-␥ and IL-17A concentrations in stimulated plasma from whole blood or supernatants from PBMC cultures were determined using commercial ELISA-based kits (Bovigam IL-17 ELISPOT assay. The protocol for the IL-17A enzyme-linked immunosorbent spot (ELISPOT) assay was as described previously (36). Briefly, 2 ϫ 10 5 PBMCs were added to polyvinylidene difluoride 96-well assay plates (Millipore, Watford, United Kingdom) that had been coated with anti-bovine IL-17A polyclonal antibodies (5 g/ml; Kingfisher Biotech) and were incubated in the presence or absence of 10 g/ml M. bovis PPD, 3 g/ml rAg85A-rTB10.4, or 3 g/ml rESAT-6:CFP10.…”
Section: Figmentioning
confidence: 99%
“…In lung granulomas in the bovine tuberculosis model [42] the cd T cells are WC1 + [43]. A particular subpopulation of the WC1 + cd T cells known as WC1.1 + cd T cells also increase in number in lungs and upper respiratory tract of cattle vaccinated with the M. bovis BCG intranasally [47] while during infections with the virulent strains of M. bovis, both major WC1 + subpopulations (WC1.1 + and WC1.2 + ) accumulate, along with WC1 À cells [47,48]. Because of the propensity of the WC1 + cd T cells to produce IFN-c it may not be surprising that depleting the WC1 + cd T cells from M. bovis-infected cattle shifts the immune response away from a type 1 or Th1 response [29].…”
Section: Responses Of Wc1 + and Wc1 à Bovine CD T Cells To Mycobactermentioning
confidence: 99%
“…Subsets of bovine WC1 + cd T cells also have been shown to have regulatory activity through cytokine secretion [30,31] although the contribution of this subpopulation to Johne's disease progression has not been investigated. both WC1 + and WC1 À cd T cells [37,48]. For example, cd T cells from M. bovis infected cattle proliferate and produce IFNc in response to non-protein mycobacterial antigens lipoarabinomannan (LAM) and mycolyl-arabinogalactan peptidoglycan (mAGP) [48].…”
Section: Responses Of Wc1 + and Wc1 à Bovine CD T Cells To Mycobactermentioning
confidence: 99%
“…After Virus Genes (2015) 51:198-208 199 [17]. GAPDH was used as a reference gene for the Vero cells and BEAS-2B, while RPS9 was used as the housekeeping gene for MDBK cells [18]. All primer sequences are listed in Table 1.…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%